Current status of nutritional literacy and influencing factors for patients with age-related macular degeneration - LUO Peilin; WAN Junli; ZHANG Feng; LI Xin; BIAN Wei (陆军军医大学学报, 2023)
Objective To investigate the current status of nutritional literacy and influencing factors in patients with age-related macular degeneration (AMD). Methods A total of 240 AMD patients were subjected with convenience sampling from a tertiary-level hospital in Chongqing from July 2022 to February 2023.General information questionnaire, Nutritional Literacy Scale, Nutritional Self-Efficacy Scale, Comprehension Social Support Scale, Health Beliefs Scale, Anxiety and Depression Scale, Chinese Version of Visual Function Questionnaire, Simple Coping Styles Scale, and nutritional knowledge about AMD were used to survey these patients. Results The score of Nutritional Literacy Scale was 142(113, 162).Multiple linear regression analysis showed that per capita monthly family income, visual function, depression, nutritional self-efficacy, and nutritional knowledge related to AMD were the influencing factors for nutritional literacy (P < 0.05). Conclusion The nutritional literacy level of AMD patients is quite low.The AMD patients with high per capita monthly family income, better visual function, less depression, good nutritional self-efficacy, and better nutritional knowledge related to AMD have better nutrient-literate.